Flexible ZIF-67 / PAN porous nanotube film as well as preparation method and application thereof

Loofah-shaped porous PAN nanotube membrane was prepared by electrospinning and solvent heat induction technology, and loaded ZIF-67 was grown on its surface and inside, solving the recycling and loading of MOF on the fiber membrane and achieving efficient adsorption and catalytic degradation performance.

CN119777074APending Publication Date: 2025-04-08WUHAN POLYTECHNIC UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411744658.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-01
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, MOF is difficult to recover as an adsorbent, and the surface of the electrospinned fiber membrane is smooth, and the MOF is easily fallen off and cannot be loaded.

Method used

Electrospinning technology was used to prepare PAN/PVP nanofiber membranes, and loofah-shaped porous PAN nanotube membranes were prepared through solvent-induced reactions, combining in situ growth strategies to load ZIF-67 on the fiber surface and internally.

Benefits of technology

The prepared ZIF-67/PAN porous nanotube membrane has excellent selective adsorption and catalytic degradation properties, which can effectively adsorb and separate organic pollutants, and significantly improve the degradation efficiency of organic pollutants in the presence of PMS.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777074A_ABST
    Figure CN119777074A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ZIF-67 loaded nanotube membranes, and discloses a flexible ZIF-67 / PAN porous nanotube membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving polyacrylonitrile and polyvinylpyrrolidone in N, N-dimethylformamide, and stirring to obtain a uniform precursor spinning solution; the precursor spinning solution is subjected to electrostatic spinning and drying treatment, and a PAN / PVP nanofiber membrane is obtained; cutting the PAN / PVP nanofiber membrane according to a preset size, adding ethylene glycol, and carrying out a solvothermal induction reaction to obtain a bionic loofah sponge-shaped flexible porous PAN nanotube membrane; the preparation method comprises the following steps: dissolving cobalt nitrate hexahydrate in methanol to prepare a solution A, dissolving 2-methylimidazole in methanol to prepare a solution B, soaking a bionic loofah sponge-shaped flexible porous PAN nanotube membrane in the solution A, then adding the solution B, and slowly oscillating to obtain the ZIF-67 / PAN flexible porous nanotube membrane loaded with ZIF-67 on the surface. The ZIF-67 / PAN flexible porous nanotube film is applied to catalytic degradation and selective adsorption of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanotube membranes loaded with ZIF-67, and in particular to a flexible ZIF-67 / PAN porous nanotube membrane and a preparation method and application thereof. Background Art

[0002] At present, relevant personnel have studied a large number of wastewater treatment and carbon emission reduction technologies, including membrane separation, catalytic oxidation technology, adsorption, etc. Among them, adsorption technology is regarded as one of the best methods for wastewater treatment and greenhouse gas adsorption applications due to its advantages such as high efficiency, high selectivity and low energy consumption. Metal organic framework compounds (MOF) are considered to be an ideal and efficient adsorbent due to their designable structure, adjustable pores, large specific surface area, high porosity and other characteristics. Among them, ZIF-67 (Co) is a metal organic framework, a crystalline material with a porous structure formed by metal ions (cobalt) and organic ligands through coordination bonds. However, MOF is generally a powder material, which is difficult to recover after being dispersed in water. Therefore, introducing MOF onto a solid substrate to prepare an easily separable material is an effective solution.

[0003] Polyacrylonitrile (PAN) is widely used as a precursor of nano carbon fiber because of its low cost, good spinning performance and high carbonization rate. It has a very broad application prospect in the field of preparing functional materials such as electromagnetic wave absorption, catalysis and antibacterial. Electrospinning is a simple method for preparing membrane materials, and the resulting fiber is in the form of a non-woven fabric with good porosity, which is conducive to the immersion of MOF seed solution. However, when using electrospinning fiber membrane as a substrate to load MOF, the fiber surface is relatively smooth, MOF is easy to fall off, and MOF cannot be loaded. Therefore, the present application provides a kind of green and economic porous flexible nanotube membrane with rough structure surface to solve the above problems. Summary of the invention

[0004] Based on the above, the purpose of the present invention is to provide a flexible ZIF-67 / PAN porous nanotube membrane and its preparation method and application, and to load ZIF-67 onto the PAN porous nanotube membrane. The ZIF-67 / PAN porous nanotube membrane has excellent selective adsorption performance and catalytic degradation performance.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a flexible ZIF-67 / PAN porous nanotube membrane comprises the following steps:

[0007] Dissolving polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) in N,N-dimethylformamide (DMF) and stirring to obtain a uniform precursor spinning solution; electrospinning the precursor spinning solution and drying to obtain a PAN / PVP nanofiber membrane;

[0008] The PAN / PVP nanofiber membrane is cut into a preset size, placed in a high-pressure reactor, ethylene glycol is added, a solvent thermal induction reaction is carried out, and then repeatedly washed with deionized water to obtain a biomimetic loofah-like flexible porous PAN nanotube membrane;

[0009] The cobalt nitrate hexahydrate is dissolved in methanol to prepare solution A, and 2-methylimidazole is dissolved in methanol to prepare solution B. The biomimetic luffa-like flexible porous PAN nanotube membrane is immersed in the solution A, and then the solution B is slowly added into the solution A soaked with the biomimetic luffa-like flexible porous PAN nanotube membrane, and the solution is slowly shaken. The product is collected by centrifugation and washed multiple times, and vacuum dried to obtain a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface.

[0010] As a preferred solution for the preparation of a flexible ZIF-67 / PAN porous nanotube membrane, the mass ratio of PAN to PVP is 1:1, the concentration of PAN relative to DMF is 1 g / mL; the concentration of PAN relative to ethylene glycol is 0.3 g / mL.

[0011] As a preferred solution for the preparation of a flexible ZIF-67 / PAN porous nanotube membrane, during the electrospinning process, a collecting device is used to collect the electrospinning product, the spinning temperature is 20-30°C, the relative humidity is 40-50%, and a 11-13 kV DC high voltage is connected.

[0012] As a preferred solution of the method for preparing a flexible ZIF-67 / PAN porous nanotube membrane, in the drying process after electrospinning, the drying temperature is 50 to 70° C. and the drying time is 1 to 3 hours.

[0013] As a preferred solution of the method for preparing a flexible ZIF-67 / PAN porous nanotube membrane, during the solvent thermal induction reaction, the reaction temperature is 170 to 190° C. and the reaction time is 2 to 4 hours.

[0014] As a preferred scheme for the preparation method of a flexible ZIF-67 / PAN porous nanotube membrane, in the solution A, the molar concentration of the cobalt nitrate hexahydrate relative to the methanol is 0.05-0.4 mmol / L; in the solution B, the molar concentration of the 2-methylimidazole relative to the methanol is 0.4-3.2 mmol / L; the molar ratio of the cobalt nitrate hexahydrate to the 2-methylimidazole is 1:8.

[0015] As a preferred solution of the method for preparing a flexible ZIF-67 / PAN porous nanotube membrane, the mass ratio of the cobalt nitrate hexahydrate to the bionic loofah-like porous nanotube membrane is (7-60):1.

[0016] As a preferred solution of the method for preparing a flexible ZIF-67 / PAN porous nanotube membrane, the vacuum drying process is carried out at 50 to 70° C. for 10 to 14 hours.

[0017] A flexible ZIF-67 / PAN porous nanotube membrane is prepared by any of the above-mentioned preparation methods.

[0018] The invention discloses an application of a flexible ZIF-67 / PAN porous nanotube membrane. Based on the flexible ZIF-67 / PAN porous nanotube membrane, the membrane is applied in the catalytic degradation and selective adsorption of organic pollutants.

[0019] The beneficial effects of the present invention are:

[0020] The invention provides a flexible ZIF-67 / PAN porous nanotube membrane and a preparation method and application thereof. The PAN / PVP nanofiber membrane is prepared by utilizing electrostatic spinning technology, and a PVP component is selectively removed by thermal induction of ethylene glycol (EG) solvent to prepare a PAN-based porous nanotube with a loofah-like structure. The porous structure of the hollow tube and the tube wall surface can better adsorb and complex cobalt ions and reaction reagents. The ZIF-67 is in situ loaded on the inner wall and surface of the PAN porous nanotube with a loofah-like structure by utilizing an in-situ growth strategy to obtain the ZIF-67 / PAN nanotube membrane. The loofah-like flexible PAN porous nanotube membrane not only provides a good foundation for the in-situ growth of ZIF-67 on the surface of the hollow tube, but also provides a growth space for ZIF-67 inside the tube.

[0021] When the concentration of ZIF-67 seed solution was 0.05 mmol / L, the prepared ZIF-67 / PAN-0.05M had the best loading condition and the largest specific surface area, which was 971.781 m 2 ·g -1In the adsorption experiment, ZIF-67 / PAN-0.05M showed the largest MO adsorption and the largest CO2 adsorption, which were 4.95 mg·g -1 and 1.28mmol·g -1 , and the material exhibits good selective adsorption performance and can well separate MO and MB mixed solutions.

[0022] In the presence of PMS, ZIF-67 / PAN-0.05M can degrade 90% of 40 mg / L TC solution within 30 min, and its reaction rate constant (0.073 min -1 ) is the presence of only PMS (0.014min -1 ) case, showing good catalytic PMS performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.

[0024] Figure 1 are (A) FT-IR and (B) XRD spectra of different examples;

[0025] Figure 2 are SEM images of different examples, (A) PAN / PVP, (B) loofah-like porous PAN fibers, (C) ZIF-67 / PAN-0.025M, (D) ZIF-67 / PAN-0.05M, (E) ZIF-67 / PAN-0.075M, (F) ZIF-67 / PAN-0.1M, (G) ZIF-67 / PAN-0.2M, (H) ZIF-67 / PAN / PVP-0.05M (the insets in E and H are enlarged images in the circles);

[0026] Figure 3 are N2 adsorption-desorption curves of different examples;

[0027] Figure 4 (A) The time-varying curve of the adsorption of MO by different materials, (B) the first-order kinetic fitting, and (C) the second-order kinetic fitting;

[0028] Figure 5 (A) Effect of solution pH on MO adsorption performance of ZIF-67 / PAN-0.05M, (B) Cyclic MO adsorption performance of ZIF-67 / PAN-0.05M;

[0029] Figure 6 (A) is a diagram of a device for separating mixed dye solutions; three-dimensional fluorescence spectra of sample solutions at different times, (B) 0min, (C) 50min, (D) 100min;

[0030] Figure 7 is the Zate potential of ZIF-67 and ZIF-67 / PAN-0.05M;

[0031] Figure 8 The CO2 adsorption curves of different materials at (A) 273K and (B) the maximum CO2 adsorption capacity at 273K and 101kPa.

[0032] Fig. 9 (A) TC degradation efficiency in different systems and the corresponding (B) pseudo-first-order kinetic constant bar graph. DETAILED DESCRIPTION

[0033] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.

[0034] The present invention provides a method for preparing a flexible ZIF-67 / PAN porous nanotube membrane, comprising the following steps:

[0035] S100, dissolving polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) in N,N-dimethylformamide (DMF) and stirring to obtain a uniform precursor spinning solution; electrospinning the precursor spinning solution, drying it, and obtaining a PAN / PVP nanofiber membrane;

[0036] Specifically, the mass ratio of PAN to PVP is 1:1, and the concentration of PAN in the DMF is 1 g / mL; during the electrospinning process, the collecting device is placed 15 to 20 cm away from the needle tip of the syringe, the spinning temperature is 20 to 30° C., the relative humidity is 40 to 50%, and a 11 to 13 kV DC high voltage is connected. Among them, the Mw of polyvinyl pyrrolidone is preferably 1,300,000, and the Mw of polyacrylonitrile is preferably 150,000.

[0037] Specifically, during the drying process after electrospinning, the drying temperature is 50-70° C. and the drying time is 1-3 hours.

[0038] S200, cutting the PAN / PVP nanofiber membrane according to a preset size, placing it in a high-pressure reactor, adding ethylene glycol, performing a solvent thermal induction reaction, and then repeatedly washing it with deionized water to obtain a bionic loofah-like flexible PAN porous nanotube membrane;

[0039] Specifically, the concentration of PAN relative to ethylene glycol was 0.3 g / mL.

[0040] Specifically, during the solvent thermal reaction, the reaction temperature is 170-190° C. and the reaction time is 2-4 hours.

[0041] S300. Dissolve cobalt nitrate hexahydrate in methanol to prepare solution A, and dissolve 2-methylimidazole in methanol to prepare solution B; soak 50 mg of biomimetic luffa-like flexible PAN porous nanotube membrane in solution A, and then slowly add solution B into solution A soaked with biomimetic luffa-like flexible porous PAN nanotube membrane, slowly shake, collect the product by centrifugation, wash it with anhydrous ethanol for multiple times, and vacuum dry it to obtain a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface.

[0042] Specifically, in solution A, the molar concentration of cobalt nitrate hexahydrate relative to methanol is 0.05-0.4 mmol / L; in solution B, the molar concentration of 2-methylimidazole relative to methanol is 0.4-3.2 mmol / L; and the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:8.

[0043] Specifically, the mass ratio of cobalt nitrate hexahydrate to the bionic loofah-like porous nanotube membrane is (7-60):1.

[0044] Specifically, during the vacuum drying process, the reaction is carried out at 50 to 70° C. for 10 to 14 hours.

[0045] The present invention will be further described below by means of specific examples.

[0046] Example 1

[0047] 0.6g PAN and 0.6g PVP were dissolved in 6mL DMF and stirred for 6h to obtain a uniform precursor spinning solution; the precursor spinning solution was transferred to a steel needle syringe connected to a 12kV DC high voltage, and the collection device was electrospun at a distance of 15cm from the tip of the steel needle. The electrospinning conditions were: temperature 25℃, relative humidity 45%. The spun nanofiber membrane was placed in an oven at 60℃ for 2h to remove the residual solvent to obtain a PAN / PVP nanofiber membrane;

[0048] The PAN / PVP nanofiber membrane was cut into small square pieces with a side length of 3 cm according to the preset size, placed in a stainless steel high-pressure reactor lined with Teflon, and 20 mL of ethylene glycol was added for high-temperature reaction. The reaction was sealed and reacted at 180 ° C for 2 h, and then repeatedly washed with deionized water to obtain a bionic loofah-like flexible porous PAN nanotube membrane.

[0049] 0.7276 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was dissolved in 25 ml of methanol to prepare solution A; 1.6422 g of 2-methylimidazole (2-MeIM) was dissolved in 25 ml of methanol to prepare solution B, wherein n Co(NO3)2·6H2O :n 2-MeIM =1:8, 50 mg of biomimetic luffa-like flexible porous PAN nanotube membrane was immersed in solution A for 30 min to make Co 2+ It was fully captured by PAN and penetrated into the inner wall of the fiber, and then solution B was slowly added to solution A soaked with bionic loofah-like flexible porous PAN nanotube membrane, and slowly shaken for 1 hour at room temperature. The product was collected by centrifugation and washed with anhydrous ethanol several times, and vacuum dried at 60°C for 12 hours to obtain a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface, which was recorded as ZIF-67 / PAN-0.05M porous fiber membrane.

[0050] Example 2

[0051] The preparation process and reaction conditions were basically the same as those in Example 1, wherein 0.3638 g of Co(NO3)2·6H2O was dissolved in 25 ml of methanol to prepare solution A; 0.8211 g of 2-MeIM was dissolved in 25 ml of methanol to prepare solution B, and a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface was obtained, which was recorded as ZIF-67 / PAN-0.025M porous fiber membrane.

[0052] Example 3

[0053] The preparation process and reaction conditions were basically the same as those in Example 1, wherein 1.0914 g of Co(NO3)2·6H2O was dissolved in 25 ml of methanol to prepare solution A; 2.4633 g of 2-MeIM was dissolved in 25 ml of methanol to prepare solution B, to obtain a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface, denoted as ZIF-67 / PAN-0.075M porous nanotube membrane.

[0054] Example 4

[0055] The preparation process and reaction conditions were basically the same as those in Example 1, wherein 1.4552 g of Co(NO3)2·6H2O was dissolved in 25 ml of methanol to prepare solution A; 3.2844 g of 2-MeIM was dissolved in 25 ml of methanol to prepare solution B, to obtain a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface, denoted as ZIF-67 / PAN-0.1M porous fiber membrane.

[0056] Example 5

[0057] The preparation process and reaction conditions were basically the same as those in Example 1, wherein 2.9103 g of Co(NO3)2·6H2O was dissolved in 25 ml of methanol to prepare solution A; 6.5688 g of 2-MeIM was dissolved in 25 ml of methanol to prepare solution B, to obtain a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface, denoted as ZIF-67 / PAN-0.2M porous nanotube membrane.

[0058] In order to further illustrate the key points of this patent, a comparative case is added for illustration.

[0059] Comparative Example 1

[0060] The preparation process and reaction conditions were basically the same as those in Example 1, wherein the loofah-like porous nanotube membrane was replaced with a PAN / PVP nanofiber membrane to obtain a ZIF-67 / PAN / PVP porous fiber membrane loaded with ZIF-67 on the surface, which was recorded as ZIF-67 / PAN / PVP-0.05M fiber membrane.

[0061] Comparative Example 2

[0062] 0.05 mmol (1.4552 g) of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was dissolved in 25 ml of methanol to prepare solution A; 0.4 mmol (3.2844 g) of 2-methylimidazole (2-MeIM) was dissolved in 25 ml of methanol to prepare solution B. Solution B was then slowly added to solution A and slowly shaken at room temperature for 1 h. The product was collected by centrifugation and washed several times with anhydrous ethanol. Drying was performed at 60°C in a vacuum oven for 12 h to obtain dry ZIF-67.

[0063] The preparation formulas of the porous fiber membranes prepared in the above examples and comparative examples are shown in Table 1.

[0064] Table 1 Preparation formula of different examples

[0065]

[0066]

[0067] In order to further study the antibacterial properties of the ZIF-67 / PAN porous fiber membrane prepared in the present application and its catalytic degradation performance on organic pollutants, antibacterial experiments and catalytic degradation experiments were carried out on the products prepared in the above examples.

[0068] 1. Adsorption experiment

[0069] Prepare 20 mg / L methyl orange (MO) solution, put 50 mg of ZIF-67 / PAN-X porous fiber membrane into 50 mL MO solution, and shake at room temperature. Take appropriate amount of supernatant at given time intervals, and measure the absorbance at 464 nm using UV-visible spectrophotometer. The maximum adsorption capacity Q e Calculated by the following formula:

[0070]

[0071] In the formula, C0 (mg / L), C t (mg / L) are the initial concentration and concentration of MO solution at time t, m (mg) is the mass of the adsorbent, and V (mL) is the volume of the solution.

[0072] In order to investigate the selective adsorption performance of ZIF-67 / PAN-0.05M, the same volume of MO and MB solutions (both with a concentration of 20 mg / L) were mixed to obtain solution C. Figure 5 The device shown in (A) circulates and filters solution C. A small amount of the supernatant is taken at a certain time point and detected using a three-dimensional fluorescence instrument.

[0073] The CO2 adsorption capacity of different examples at 273K and 0-101kPa pressure range was tested using a volume meter.

[0074] 2. Catalytic degradation experiment

[0075] Tetracycline (TC) was used to simulate organic pollutants, and all catalytic degradation experiments were carried out at room temperature and in the dark. First, 5 mg of catalyst was added to 50 mL of 40 mg / L TC solution and shaken for 30 minutes to reach adsorption-desorption equilibrium. Then, 20 mg of PMS was added to start the catalytic degradation reaction. At regular intervals, 3 mL of the supernatant was added to a centrifuge tube containing 1 mL of methanol to quench the reaction. After filtering through a 0.45 μm microporous membrane, the absorbance of the supernatant was detected at 357 nm using a UV-visible spectrophotometer. As a comparison, a degradation experiment with only 20 mg of PMS was performed under the same conditions.

[0076] In addition, in order to further analyze the reaction mechanism and product performance, relevant performance analysis was also performed on the products prepared in the examples and comparative examples of the present application.

[0077] 1. Component and structure analysis

[0078] The functional group composition of the material was tested using Fourier transform infrared spectrometer. Figure 1 (A) As shown in Figure 2, the wavelengths of PAN porous nanofibers at 3400, 3000-2900 and 1454 cm -1 There are obvious absorption peaks near 2245cm and 1450cm, which belong to -OH stretching vibration, CH bond stretching vibration and deformation vibration. -1 The peak at 992 cm-1 corresponds to the stretching vibration of the C≡N bond and the stretching vibration of C=C in PAN. -1 、1418cm -1 、1303cm -1 、1575cm -1 、2925cm -1 、3134cm -1 and 3442cm -1 The FT-TR bands observed at 100 nm are attributed to the vibration absorption of various groups in 2-MeIM in ZIF-67. The above two characteristic peaks appeared in the ZIF-67 / PAN-X example, indicating that PAN remained stable while ZIF-67 was loaded.

[0079] The successful loading of ZIF-67 was further verified by XRD, such as Figure 1 As shown in (B), the PAN nanofiber membrane without ZIF-67 loading has only one peak at 2θ=18°, which is attributed to the characteristic peak of PAN hexagonal structure. Pure ZIF-67 has diffraction characteristic peaks at 2θ=7.39°, 10.45°, 12.80°, 14.75°, 16.55°, 18.10°, 24.60°, 26.80°, 29.80°, 30.75° and 32.55°, corresponding to (011), (002), (112), (022), (013), (222), (233), (134), (044), (334) and (235) crystal planes, respectively. ZIF-67 / PAN-X has the same characteristic diffraction peaks as ZIF-67. Combined with the FT-IR characterization results, it is shown that this method can successfully load ZIF-67.

[0080] 2. Morphology analysis

[0081] The growth state of ZIF-67 on the fiber surface was observed using a scanning electron microscope. Figure 2(A) shows that the surface of PAN / PVP nanofiber membrane is smooth and the diameter is uniformly about 300nm. After 2h of EG solvent thermal induction, PAN nanofibers with unique loofah-like porous morphology were obtained, and the material still maintained the original one-dimensional fiber state well. The average diameter of the fiber increased to about 930nm ( Figure 2 (B) This may be due to the swelling of the fiber during the removal of PVP. This rough surface and internal porous structure not only allows ZIF-67 to grow on the fiber surface and not fall off easily, but also provides growth space inside the fiber. Figure 2 (CH) is the surface morphology of different ZIF-67 / PAN-X porous nanotube membranes obtained by in situ growth. It can be clearly seen that a large amount of ZIF-67 is loaded on the fiber surface, and a small amount of ZIF-67 exists between the fibers, indicating that this method can successfully load ZIF-67 on the fiber. However, it is not difficult to find that with the continuous increase in the concentration of the seed solution for synthesizing ZIF-67, the amount of ZIF-67 on the fiber surface increases first and then decreases. The reason may be that at the beginning, the concentration is small and the synthesized ZIF-67 is small. As the concentration increases, more ZIF-67 is loaded on the fiber. After that, the concentration continues to increase, and the fiber surface can no longer provide growth space. More MOF precursors can only form uniform self-nucleation and then grow into larger ZIF-67 crystals. The fiber is difficult to provide more space and difficult to support its weight, resulting in a large amount of ZIF-67 crystals falling off. Figure 2 (D) and Figure 2 (H) shows the growth on the surface of loofah-like PAN porous nanofibers and PAN / PVP nanofibers under the same concentration conditions (0.05M). It can be seen from the enlarged image that ZIF-67 grown on the PAN / PVP surface is more compact, while ZIF-67 on the surface of loofah-like porous PAN fibers is more dispersed. This may be because the fiber diameter of the latter is larger, and the surface can provide more space for the growth of ZIF-67, and the interior may also provide growth space for ZIF-67. This is more conducive to increasing the specific surface area of ​​the material, and it can also improve the contact efficiency of ZIF-67 with the external environment.

[0082] 3. Specific surface area analysis

[0083] from Figure 3It can be seen that the PAN / PVP nanofiber membrane shows a type III isotherm and is a typical non-porous or macroporous material. The data detected in the pore size distribution comes from the pores formed by the interlaced packing between different nanofibers. After the hydrothermal induction treatment with EG solvent, obvious hysteresis loops appear in the loofah-like porous PAN fiber membrane in the range of 0.8 < P / P0 < 1.0, indicating that the sample has a mesoporous structure. The specific surface areas of the first two are relatively small (both less than 30 m 2 ·g -1 ). ZIF-67 has an extremely large specific surface area (1322.547 m 2 ·g -1 ), showing an obvious type I isotherm. The adsorption of N2 is basically completed at a low relative pressure (P / P0 < 0.2), which is one of the main characteristics of microporous materials. After the in-situ loading of ZIF-67, the specific surface areas of ZIF-67 / PAN-X all increase to more than 700 m 2 ·g -1 and above, while showing an obvious type I isotherm and hysteresis loops appearing in the range of 0.8 < P / P0 < 1.0, further indicating the successful loading of ZIF-67 on the loofah-like porous PAN fiber membrane. From the data in Table 2, it can be seen that the specific surface area of ZIF-67 / PAN-X first increases and then decreases, and the maximum can reach 72% of pure ZIF-67.

[0084] Table 2 Physical properties of different samples

[0085]

[0086] 4. Analysis of adsorption performance and adsorption mechanism

[0087] Figure 4 (A) shows the curves of the adsorption amount of MO by different materials changing with time. It can be seen that the loofah-like porous PAN has almost no adsorption effect on MO. After loading ZIF-67, the adsorption amount increases sharply, indicating that ZIF-67 is the main adsorbent. The adsorption capacity of ZIF-67 / PAN-X increases sharply within the first 100 min, almost reaching 90% of the equilibrium adsorption capacity. After that, the adsorption amount increases slowly until the adsorption-desorption equilibrium is reached at about 180 min. Among them, ZIF-67 / PAN-0.05M shows the best adsorption performance, attributed to its largest specific surface area and more and more dispersed ZIF-67 loading. While the adsorption performance of ZIF-67 / PAN / PVP-0.05M is the weakest, which may be because the ZIF-67 on the surface of this material agglomerates together and does not contact the MO molecules sufficiently. To evaluate the adsorption kinetic behavior of the materials, the pseudo-first-order kinetic model and the pseudo-second-order kinetic model were respectively used to fit the experimental data ( Figure 4(B, C)), Table 3 gives the specific parameters obtained by fitting and their correlation coefficients R 2 The fitting degree of the kinetic data to the pseudo-first-order kinetic model is low, indicating that the model is not suitable for the current adsorption system. The pseudo-second-order kinetic model has a high correlation coefficient with the experimental data. This shows that the pseudo-second-order kinetic model can better describe the adsorption behavior of MO on ZIF-67 / PAN-X.

[0088] Table 3 Kinetic model parameters for different materials

[0089]

[0090] The MO absorption capacity of ZIF-67 / PAN-0.05M under different pH conditions Figure 5 (A). It can be seen that when the solution pH = 7, the strongest adsorption performance is shown. When the solution pH = 4, 75% of the optimal performance can be maintained, indicating that the material can still maintain relatively good stability in a weak acid environment. As the pH increases to 10, the adsorption performance of MO decreases significantly, and only 52% of the optimal performance is maintained. This may be because the electrostatic adsorption between ZIF-67 and MO is affected under alkaline conditions, and the adsorption effect comes more from the large specific surface area of ​​ZIF-67 itself. In summary, the material can still maintain good performance in a weak acid environment, and the material performance is significantly weakened in an alkaline environment. Neutral conditions are most suitable for the adsorption of MO on ZIF-67 / PAN-0.05M. The performance of ZIF-67 / PAN-0.05M was further evaluated through cyclic adsorption experiments, and a MO solution with an initial concentration of 20 mg / L was selected for three cycles of adsorption. The results are shown in Figure 5 As shown in (B), ZIF-67 / PAN-0.05M still maintains more than 80% of its initial performance after 3 cycles, indicating that ZIF-67 / PAN-0.05M has good stability.

[0091] Use Figure 6 (A) The device shown in Figure 1 tests the separation performance of ZIF-67 / PAN-0.05M for mixed dyes of MO and MB. It can be seen that the initial mixed dye is green. As time goes by, MO is gradually adsorbed, the orange gradually fades, and the solution turns blue, indicating that the material has the ability to separate MO and MB. The sample solution at different times was further detected using three-dimensional fluorescence, such as Figure 6As shown in (B), MO has a characteristic peak in the range of Em / Ex=300-400nm / 200-300nm, and MB has obvious characteristic peaks at Em / Ex=650-800nm / 200-350nm and Em / Ex=650-800nm / 450-700nm. As time goes by, the characteristic peak of MO gradually weakens until it disappears, while the characteristic peak of MB remains almost unchanged, indicating that ZIF-67 / PAN-0.05M only adsorbs MO, and a large amount of MB still remains in the solution, proving the good separation performance of the material.

[0092] In order to understand its selective adsorption mechanism, Zeta potential was used to measure and evaluate the potential of the material. Figure 7 As shown, the charge of ZIF-67 powder is concentrated at 23.7 mV, and the surface is positively charged, while the charge of ZIF-67 / PAN-0.05M is concentrated at 1.22 mV, and the surface is positively charged. MO and MB are anionic dyes and cationic dyes, respectively. Therefore, ZIF-67 / PAN-0.05M with a positive charge on the surface has a rapid adsorption effect on MO due to electrostatic effect, while a small amount of MB dye can only be adsorbed by the larger surface area of ​​ZIF-67 / PAN-0.05M. As a result, the material can efficiently separate the mixed solution of MO and MB without any external force.

[0093] The gas capture performance of different materials was studied by single-component CO2 adsorption ( Figure 8 All examples showed a certain CO2 adsorption capacity, and the maximum CO2 adsorption capacity of pure ZIF-67 could reach 1.87 mmol·g -1 This is mainly due to its largest specific surface area and pore volume, and the micropores and mesopores provide abundant adsorption channels and storage space for CO2 molecules, which is conducive to the migration and storage of CO2 molecules. ZIF-67 / PAN-0.05M also showed strong CO2 adsorption capacity, which can reach 70% of pure ZIF-67.

[0094] 4. Analysis of catalytic degradation performance

[0095] Using TC to simulate pollutants in water, the catalytic activity of the prepared examples was evaluated by testing the efficiency of TC degradation by activated PMS in different examples within the same time. Fig. 9As shown in (A), it can be seen that when only PMS is added, the degradation rate of TC can reach about 35% within 30 minutes. This is because PMS can produce a small amount of ·O2 through self-decomposition, thereby degrading a small amount of TC molecules. After adding ZIF-67 / PAN-X, the degradation rate of TC has been significantly improved, and the maximum degradation rate can reach 90% within 30 minutes, and the reaction rate constant is increased to 5.2 times that of only PMS, which shows that this material is an efficient catalyst for activating PMS to degrade TC. In addition, this material is easy to recycle and has good application value.

[0096] In summary:

[0097] A fiber carrier with larger specific surface area and rougher surface was constructed by electrospinning combined with solvothermal strategy, and ZIF-67 was loaded on the fiber surface by in situ growth. When the concentration of ZIF-67 seed solution was 0.05mmol / L, the prepared ZIF-67 / PAN-0.05M had the best loading condition and the largest specific surface area (971.781m 2 ·g -1 )

[0098] In the adsorption experiment, ZIF-67 / PAN-0.05M showed the largest MO adsorption capacity (14.95 mg·g -1 ) and the maximum CO2 adsorption capacity (1.28mmol·g -1 ), and the material exhibits good selective adsorption performance and can well separate MO and MB mixed solutions.

[0099] In the presence of PMS, ZIF-67 / PAN-0.05M can degrade 90% of 40 mg / L TC solution within 30 min, and its reaction rate constant (0.073 min -1 ) is the only PMS (0.014min -1 ) case, showing good catalytic PMS performance.

[0100] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for preparing a flexible ZIF-67 / PAN porous nanotube membrane, characterized in that: The following steps are involved: Dissolving polyacrylonitrile and polyvinyl pyrrolidone in N,N-dimethylformamide and stirring to obtain a uniform precursor spinning solution; The precursor spinning solution is subjected to electrostatic spinning and drying to obtain a PAN / PVP nanofiber membrane; The PAN / PVP nanofiber membrane is cut into a preset size, placed in a high-pressure reactor, ethylene glycol is added, a solvent thermal induction reaction is carried out, and then repeatedly washed with deionized water to obtain a biomimetic loofah-like flexible porous PAN nanotube membrane; The cobalt nitrate hexahydrate is dissolved in methanol to prepare solution A, and 2-methylimidazole is dissolved in methanol to prepare solution B. The biomimetic luffa-like flexible porous PAN nanotube membrane is immersed in the solution A, and then the solution B is slowly added into the solution A soaked with the biomimetic luffa-like flexible porous PAN nanotube membrane, and the solution is slowly shaken. The product is collected by centrifugation and washed multiple times, and vacuum dried to obtain a ZIF-67 / PAN flexible porous nanotube membrane with ZIF-67 loaded on the surface.

2. The method for preparing the flexible ZIF-67 / PAN porous nanotube membrane according to claim 1, characterized in that: The mass ratio of the polyacrylonitrile to the polyvinyl pyrrolidone is 1:1, the concentration of the polyacrylonitrile relative to the N,N-dimethylformamide is 1 g / mL; the concentration of the polyacrylonitrile relative to the ethylene glycol is 0.3 g / mL.

3. The method for preparing the flexible ZIF-67 / PAN porous nanotube membrane according to claim 1, characterized in that: During the electrostatic spinning process, a collecting device is used to collect the electrostatic spinning product, the spinning temperature is 20-30° C., the relative humidity is 40-50%, and a 11-13 kV DC high voltage is connected.

4. The method for preparing the flexible ZIF-67 / PAN porous nanotube membrane according to claim 1, characterized in that: During the drying process after electrospinning, the drying temperature is 50-70° C. and the drying time is 1-3 hours.

5. The method for preparing the flexible ZIF-67 / PAN porous nanotube membrane according to claim 1, characterized in that: During the solvent thermal induction reaction, the reaction temperature is 170-190° C. and the reaction time is 2-4 hours.

6. The method for preparing the flexible ZIF-67 / PAN porous nanotube membrane according to claim 1, characterized in that: In the solution A, the molar concentration of the cobalt nitrate hexahydrate relative to the methanol is 0.05-0.4 mmol / L; in the solution B, the molar concentration of the 2-methylimidazole relative to the methanol is 0.4-3.2 mmol / L; the molar ratio of the cobalt nitrate hexahydrate to the 2-methylimidazole is 1:

8.

7. The method for preparing the flexible ZIF-67 / PAN porous nanotube membrane according to claim 1, characterized in that: The mass ratio of the cobalt nitrate hexahydrate to the bionic loofah-like porous nanotube membrane is (7-60):

1.

8. The method for preparing the flexible ZIF-67 / PAN porous nanotube membrane according to claim 1, characterized in that: During the vacuum drying process, the reaction is carried out at 50-70° C. for 10-14 hours.

9. A flexible ZIF-67 / PAN porous nanotube membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. An application of a flexible ZIF-67 / PAN porous nanotube membrane, characterized in that: The flexible ZIF-67 / PAN porous nanotube membrane described in claim 8 is used in the catalytic degradation and selective adsorption of organic pollutants.

Citation Information

Patent Citations

  • Method for preparing polyacrylonitrile-based porous hollow carbon fibers by coaxial electrospinning

    CN102691136A

  • Metal organic framework film for catalytic degradation on organic pollutant and preparation method of metal organic framework film

    CN107096568A

  • Porous supported electrospun nano photocatalytic fiber membrane and preparation method thereof

    CN108842304A

  • Nanofiber-loaded metal organic framework air purification material and preparation method thereof

    CN111013271A

  • Porous multi-hollow flexible composite nanofiber membrane material and preparation method thereof

    CN113073426A